Response of direct inoculation of VAM on growth, leaf yield and phosphorus uptake in mulberry (Morus alba) - SETUA, G C; KAR, R; GHOSH, J K; DAS, N K; SARATCHANDRA, M (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted at Berhampore during 1994-97 to study the effect of direct inoculation of VAM through sowing of maize seeds (40 kg/ha) coated with VAM-slurry (75 kg/ha) in between the rows of 2-year old mulberry and applying VAM-slurry (200 kg/ha) at root zone of 2-year-old ’S I’ mulberry plantation through holes. Data revealed that plant height (119.5 cm), number of leaves/plant (233.3), leaf yield (25 635.5 kg/ha/yr) and leaf ,moisture (74.4%) were found to be maximum in former method by the influence of Glomus fasclculalum with 30 kg P ha/year over the others. Phosphorus uptake was also found to be similar with the control and other treatments. Direct method of inoculation with slurry of G. fasciculatum coated on the surface of water-soaked maize seed followed by sowing and with the application of 30 kg P/ha/year was found to be very much promising in respect of quality and quantity of leafproductiort in mulberry with simultaneous reduction in use of 80% phosphate fertilizer/ha/year. Besides, an excess production of2 085 kg/ha mulberry leaves and 6-590 kg/ha green biomass of maize also fetched Rs 4 114/ha as net gain in the initial year of V AM application and Rs 5 940/ha in the following years.